Coverage of the Western Television Programmes by the Ghanaian Media: A Comparative Analysis of UTV And TV3 - Obimpeh, Prince (UniMAC-GIJ, 2020)
Since media is such a big part of people’s everyday lives, and in some ways may influence how people perceive themselves and the world (Micah, 2018), this study seeks to do a comparative analysis of the coverage of western television programs by the Ghanaian media. It is known all over the world that the images you see in films, TV shows, and advertising consciously or subconsciously influence individuals (Xin Cheng, 2001). These photos, known or unknown, can influence the way people view life and the development of their identities. It is extremely doubtful that the media does not influence the people, how they feel and how they perceive the environment they reside (Gauntlett, 2008). This is particularly noteworthy that we are in an age where representations of various phases in the scientific, political, medical and most relevant media are being promoted throughout the world. (Wilson, 1987; Olivas, 1988; Nakanishi, 1993; Smith, Wolf, and Busenberg, 1996; Meyers, 2004; Turner,2016 and Micah, 2018).
MA Journalism